PENGEMBANGAN DESA WISATA BEJIHARJO, KECAMATAN KARANGMOJO, KABUPATEN GUNUNGKIDUL - , IAN PUJI PRIYONO, I Made Krisnajaya, S.IP, MPA. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Bejiharjo Tourism Village is a tourist village which was formed in 2010 and located in District Karangmojo, Gunungkidul, Yogyakarta. The main of tourism interest is Goa Pindul, Bejiharjo Tourism Village managed to get the award from the Minister of Tourism and Creative Economy in 2012. With the magnitude of the potential, Bejiharjo village also still have some other attraction, not just Goa Pindul. Whether in the form of natural, artificial, and even culture. The success of Village Tourism Bejiharjo led the authors to conduct research related to the development of Village Tourism Bejiharjo. This research was presented by identifying the factors supporting and role of each actor involved that makes the Bejiharjo village can evolve as it is today, and presenting it in the form of qualitative descriptive writing. So it can help the reader to understand the purpose to be conveyed by the author. By this research, the authors hope to help others rural tourist village, in order to thrive as Bejiharjo Tourism Village. As well as to provide input to the government in formulating policies related to the development of rural tourism. Reputation and fame attached to Goa Pindul make another attraction that is as if covered. Visitors get to know more about Goa Pindul than Bejiharjo itself. By utilizing these conditions, the manager of Goa Pindul also use it to promote and more focus on Goa Pindul than others. This can be seen from the development of tourist facilities and activities are still centered in Goa Pindul. Even the culture of the people who initially presented in the form of tourist attraction are increasingly covered. To overcome this the manager should think about ways to restore the concept of a tourist village on the village Bejiharjo. One of them is to revitalize the appeal of other travelers as an alternative if bored with the attractions which offered by Goa Pindul. Especially the cultural appeal as a way of life Bejiharjo community. Keywords: Development, Tourism, Bejiharjo tourism village, Travelers.